2019
DOI: 10.2147/ijn.s183842
|View full text |Cite
|
Sign up to set email alerts
|

<p>Promoting tendon to bone integration using graphene oxide-doped electrospun poly(lactic-co-glycolic acid) nanofibrous membrane</p>

Abstract: Background These normal entheses are not reestablished after repair despite significant advances in surgical techniques. There is a significant need to develop integrative biomaterials, facilitating functional tendon-to-bone integration. Materials and methods We fabricated a highly interconnective graphene oxide-doped electrospun poly(lactide-co-glycolide acid) (GO-PLGA) nanofibrous membrane by electrospinning technique and evaluated them using in vitro cell assays. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 57 publications
1
36
0
2
Order By: Relevance
“…Based on ordinary fused deposition modeling (FDM) 3D printing, by increasing the electric field, the ink passing through the needle base can be further pulled, thereby breaking the aperture limit of the printing needle and achieving higher precision. In the past, electrospinning technology was used but was mostly used to prepare 2D electrospun nanofiber membranes [ [46] , [47] , [48] , [49] ]. When combined with 3D printing technology to obtain a 3D structure and achieve controlled printing, it is difficult for the wire diameter to reach the nanometer level of the nanofiber membrane, and the highest controllable precision can reach 1 μm [ 7 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on ordinary fused deposition modeling (FDM) 3D printing, by increasing the electric field, the ink passing through the needle base can be further pulled, thereby breaking the aperture limit of the printing needle and achieving higher precision. In the past, electrospinning technology was used but was mostly used to prepare 2D electrospun nanofiber membranes [ [46] , [47] , [48] , [49] ]. When combined with 3D printing technology to obtain a 3D structure and achieve controlled printing, it is difficult for the wire diameter to reach the nanometer level of the nanofiber membrane, and the highest controllable precision can reach 1 μm [ 7 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tendon-to-bone healing in rotator cuff repair is always a major problem, as is enthesis formation in all tendon repairs. 38 The healing or integration of artificial graft to bone is even more difficult, especially in reconstructing the transitional structure of the enthesis. 16,21,27 In 2014, Kim et al 21 made a structure with 4 layers to promote tendon-bone healing and found it effective in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…10,34 As a consequence, grafts have been developed to bridge the MRCT. 38 However, limited healing potential between tendon and graft or between graft and bone is still a problem. 9…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, to achieve osteoinductivity, it is necessary to add some functionalisation to the GO surface, by using, for example, poly(ethylamine) [ 141 ], poly(lactide-co-glycolide acid) [ 145 ], collagen [ 146 ], phosphates [ 147 ], hydroxyapatite [ 148 ] and silanes [ 149 ].…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%